1999
DOI: 10.1016/s0008-6363(99)00015-2
|View full text |Cite
|
Sign up to set email alerts
|

Chronic AT1 receptor blockade and angiotensin-converting enzyme (ACE) inhibition in (CHF 146) cardiomyopathic hamsters: effects on cardiac hypertrophy and survival

Abstract: In this model, losartan did not improve survival compared to placebo and quinapril and, if anything, increased mortality. Our results suggest that AT1 receptor antagonists and ACE inhibitors are not necessarily equivalent or interchangeable in terms of their effects on cardiac hypertrophy and survival in selected progressive heart failure models.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
14
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 47 publications
4
14
0
Order By: Relevance
“…The absence of significant effects from cilazapril pretreatments on cardiac lesions is consistent with previous reports showing that ACE inhibitors or AT 1 receptor blockers did not affect the degree of cardiac myolysis and fibrosis in HCMHs (Nakamura et al 1994;Bastien et al 1999;Linz and Busch 2003). Furthermore, our results showed that neither the preventive nor the curative treatments with cilazapril significantly attenuated the development of cardiac hypertrophy and HF of HCMHs.…”
Section: Discussionsupporting
confidence: 92%
“…The absence of significant effects from cilazapril pretreatments on cardiac lesions is consistent with previous reports showing that ACE inhibitors or AT 1 receptor blockers did not affect the degree of cardiac myolysis and fibrosis in HCMHs (Nakamura et al 1994;Bastien et al 1999;Linz and Busch 2003). Furthermore, our results showed that neither the preventive nor the curative treatments with cilazapril significantly attenuated the development of cardiac hypertrophy and HF of HCMHs.…”
Section: Discussionsupporting
confidence: 92%
“…In keeping with our conclusions, other observations have shown that losartan did not regress LVH associated with thoracic AC, nor improve contractile function [28,29]. Concerning other models of hypertrophy AT 1 receptor blockade did not reverse electrophysiological changes, nor prevent the development of arrhythmias [30] or improve survival [31].…”
Section: The Pathology Associated With Lvh and The Role Of Angiotensinsupporting
confidence: 87%
“…290 -292 In experimental models of HF, ACEIs modify cardiac remodeling more favorably than ARBs, [293][294][295][296] and this advantage of ACEIs is abolished by the coadministration of a kinin receptor blocker. 293,295 Angiotensin converting enzyme inhibitors have been evaluated in more than 7000 patients with HF who participated in more than 30 placebo-controlled clinical trials.…”
Section: Angiotensin Converting Enzyme Inhibitors In the Management Omentioning
confidence: 99%